Association between trauma exposure and respiratory disease-A Mendelian randomization study - Ma, Yuchao; Meng, Changjiang; Weng, Liang (Frontiers in Endocrinology, 2022)
Background Trauma is a well-known risk factor for many disease, but the effect of trauma on respiratory disease is unclarified. In the present study, we aimed to evaluate the association between trauma and respiratory disease. Method Using both United Kingdom biobank and Finnish biobank genome-wide association study data (GWAS), we performed a two-sample Mendelian randomization (MR) analysis to evaluate the relationship between trauma and respiratory disease. We used four methods including inverse-variance weighted (IVW), weighted median, Maximum likelihood, and MR-Egger in this MR analysis. The IVW MR was selected as the main method. We also performed multivariable Mendelian randomization (MVMR) to simultaneously assess the independent impact of trauma exposure on respiratory disease. Results In the main two-sample MR analysis, trauma exposure was significantly associated with increased risk of respiratory disease (OR 1.15, 95%CI: 1.05-1.25). Besides, there was no heterogeneity and horizontal pleiotropy observed in the sensitivity analysis. After adjusting for pack years of smoking and body mass index (BMI), trauma exposure retained its association with respiratory disease (OR, 1.13, 95%CI, 1.04-1.23 adjusted by pack years of smoking; and OR, 1.11, 95%CI, 1.04-1.18 adjusted by BMI). Conclusion Our study discovered the association between trauma exposure and the increased risk of respiratory disease, suggesting the prevention and treatment with trauma to reduce the risk of respiratory disease.